The impact of sleeve gastrectomy on quality of life and mental health one year after surgery: a single-center prospective cohort study - Fezzeh Elyasinia; Seyed Morteza Pourfaraji; Mohammadmahdi Abbasi; AhmadReza Soroush; Reza Eslamian; Fakhrodin Kiani; Ali Mir; Narjes Mohammadzadeh (BMC Surgery)
Abstract Objectives The prevalence of impaired health-related quality of life (HRQOL) and some mental health complications, such as anxiety and depression, were previously reported to be higher in cases with obesity. However, the prevalence and changes before and after metabolic bariatric surgery (MBS) are less well-defined in various populations of individuals with severe obesity. Methods In this prospective study, the status of HRQOL, anxiety, and depression symptoms of 32 cases with severe obesity who underwent sleeve gastrectomy (SG) were investigated one month before and one year after surgery. The assessments were performed through the Hospital Anxiety and Depression Scale (HADS) and the Impact of Weight on Quality of Life-lite (IWQOL-Lite) questionnaires. Results One year after surgery, Patients' average body mass index (BMI) decreased significantly by 9.14 kg/m2 (95% CI: -10.76; -7.52. At baseline, the incidence rates of probable/possible anxiety or depression disorders were 65.6% and 46.9%, respectively. However, these symptoms did not improve significantly after surgery. In contrast, HRQOL scores significantly improved across all domains. Conclusion The point prevalence of mental health complications appears to be relatively higher among patients who underwent MBS compared to the general population. While the surgery effectively reduced weight and improved the HRQOL of patients, the impact on anxiety and depression was insignificant. Due to the small sample size, especially the limited number of patients with abnormal HADS scores, these findings should be interpreted cautiously.